1910
DOI: 10.1056/nejm191010201631604
|View full text |Cite
|
Sign up to set email alerts
|

The Comparative Histology of Femoral Bones

Abstract: It is interesting to notice the diversity of structure present in the femurs of various animals. We have been led to think that bone is bone ; that long bones, and especially similar bones wherever they occurr, have the same structure because they are used for the same purposes. This is not true. Microscopical examinations of entire sections of femurs of forty-three different animals show that the structures and their arrangements are not at all the same.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 0 publications
4
8
0
Order By: Relevance
“…Primary bone tissue in juveniles is already invaded by mainly irregularly shaped and obliquely oriented secondary osteons in the inner and middle part of the cortex. Our observations on lagomorph bone histology essentially agree with Foote's (1911a) and Enlow & Brown's (1958) Primates -Again, Enlow & Brown (1958) were the first to describe the bone tissue of extinct primates by sampling a mandible of the fossil Paleocene Plesiolestes and long bones of modern primates. The authors described primary bone tissue formed by lamellar bone.…”
Section: Manuscript To Be Reviewedsupporting
confidence: 87%
See 1 more Smart Citation
“…Primary bone tissue in juveniles is already invaded by mainly irregularly shaped and obliquely oriented secondary osteons in the inner and middle part of the cortex. Our observations on lagomorph bone histology essentially agree with Foote's (1911a) and Enlow & Brown's (1958) Primates -Again, Enlow & Brown (1958) were the first to describe the bone tissue of extinct primates by sampling a mandible of the fossil Paleocene Plesiolestes and long bones of modern primates. The authors described primary bone tissue formed by lamellar bone.…”
Section: Manuscript To Be Reviewedsupporting
confidence: 87%
“…The long bones of Valenictus, a Pliocene walrus (Odobenidae), were described as being osteosclerotic (Deméré, 1994). Nakajima & Endo 2013 Euarchontoglires -Rodentia -Early contributions to rodent bone histology were made by Foote (1911a), Enlow & Brown (1958) as well as Singh, Tonna & Gandel (1974). More recent works are by Klevezal (1996) Thin sections of the femur of the dormouse Leithia sp.…”
Section: Manuscript To Be Reviewedmentioning
confidence: 99%
“…Schaffer also investigated Artiodactyla ( Sus scrofa, Capreolus ), Carnivora ( Ursus spelaeus ), Rodentia ( Arvicola ), as well as undetermined long and skull bones, all from the Pleistocene. Foote (1911a) and Foote (1911b) examined in a comprehensive study the femoral bone cortex of extant amphibians, birds, and mammals including marsupials, rodents, lagomorphs, carnivorans, ‘ungulates’, and primates. Nopcsa & Heidsieck (1934) studied reptile bones and the ribs of sirenians ( Halitherium ).…”
Section: Mammalian Bone Histology—work Before 1935mentioning
confidence: 99%
“…This was later reinforced by Foote, who showed that the femur is particularly responsive to the functional demands of the animal, including the stresses and strains to which the bone is exposed and the position of the femur relative to the body (Foote, 1911). Major limb bones, such as the femur, support the weight of an individual's body and must also contend with more acute forces experienced during locomotion.…”
Section: Introductionmentioning
confidence: 98%